Effects of guanidinoacetic acid supplementation on liver and breast muscle fat deposition, lipid levels, and lipid metabolism-related gene expression in ducks - Wu, Hongzhi; Xie, Jiajun; Peng, Weiqi; Ji, Fengjie; Qian, Jinyu; Shen, Qian; Hou, Guanyu (Frontiers in Veterinary Science, 2024)
Exogenous supplementation of guanidinoacetic acid can mechanistically regulate the energy distribution in muscle cells. This study aimed to investigate the effects of guanidinoacetic acid supplementation on liver and breast muscle fat deposition, lipid levels, and lipid metabolism-related gene expression in ducks. We randomly divided 480 42-day-old female Jiaji ducks into four groups with six replicates and 20 ducks for each replicate. The control group was fed the basal diet, and the experimental groups were fed the basal diet with 400, 600, and 800 mg/kg (GA400, GA600 and GA800) guanidinoacetic acid, respectively. Compared with the control group, (1) the total cholesterol (P = 0.0262), triglycerides (P = 0.0357), malondialdehyde (P = 0.0452) contents were lower in GA400, GA600 and GA800 in the liver; (2) the total cholesterol (P = 0.0365), triglycerides (P = 0.0459), and malondialdehyde (P = 0.0326) contents in breast muscle were decreased in GA400, GA600 and GA800; (3) the high density lipoprotein (P = 0.0356) and apolipoprotein-A1 (P = 0.0125) contents were increased in GA600 in the liver; (4) the apolipoprotein-A1 contents (P = 0.0489) in breast muscle were higher in GA600 and GA800; (5) the lipoprotein lipase contents (P = 0.0325) in the liver were higher in GA600 and GA800;(6) the malate dehydrogenase contents (P = 0.0269) in breast muscle were lower in GA400, GA600, and GA800; (7) the C20:0 (P = 0.0235), C20:1 n9 (P = 0.0381), C20:2 (P = 0.0269), C20:3 n3 (P = 0.0453) proportions in breast muscles were higher in GA400, GA600, and GA800; (8) the Insulin induced gene 1 (P = 0.0326), Fatty acid transport protein 1 (P = 0.0412), and Lipoprotein lipase (P = 0.0235) relative expression were higher in GA400, GA600, and GA800 in the liver; (9) the Insulin induced gene 1 (P = 0.0269), Fatty acid transport protein 1 (P = 0.0234), and Lipoprotein lipase (P = 0.0425) relative expression were increased in GA400, GA600, and GA800 in breast muscle. In this study, the optimum dosage of 600 mg/kg guanidinoacetic acid improved the liver and breast muscle fat deposition, lipid levels, and lipid metabolism-related gene expression in ducks.